The effect of six weeks hamstring eccentric exercises on the postural control ability and knee joint proprioception in adolescent football players. - Azita Mohamadi; Amir Letafatkar; Seyed Hosein Hosseini; Safoura Heshmati (Biyumikānīk-i varzishī)
Objective: Football players are more likely to suffer from lower limbs injuries than other athletes; on the other hand, they need a high level of coordination, postural control, strength and range of motion to achieve optimal performance. The purpose of this study was to evaluate the effect of six weeks hamstring eccentric exercises on the postural control ability and knee joint proprioception in adolescent football players. Methods: In this semi-experimental study, 30 male football players who scored below 14 in functional screening tests were selected and divided equally into two groups. Before and after exercises, the knee proprioception and hip flexion range of motion were measured by goniometry and dynamics postural control ability was measured by the Y-test. Data were analyzed using analysis covariance. Results: According to the results, there were no significant differences in the knee proprioception, dynamic postural control and hip flexion range of motion between the experimental and control groups in the pre-test (p> 0.05). In the post-test, there was no significant difference between the experimental and control groups in the knee active proprioception (p >0.05), but the knee passive proprioception (p = 0.014), dynamic postural control (P = 0.001) and hip flexion range of motion (p = 0.003), were significantly improved in experimental group. Conclusion: Based on the results, hamstring eccentric exercises can improve the knee proprioception, postural control and hip flexion range of motion in the football players. Therefore, in order to improving the athletic performance and preventing the injuries occurrence, such exercises can be included in the training programs of these athletes.